A numerical study on the effects of moving regenerator to the performance of a β-type Stirling engine. (April 2015) - Chen, Wen-Lih; Wong, King-Leung; Chang, Yu-Feng
Abstract: An in-house CFD code has been developed to study the effects of a moving regenerator on the performance of a β -type Stirling engine. The results include temperature contours, variations of average temperature, heat transfer rates, integrated rates of heat input and output, engine power, and efficiency. It is found that the moving regenerator acts as an effective thermal barrier between the expansion and compression chambers, resulting in significant reduction in rates of heat input and output and promotion on engine's indicated power. However, the porous medium in the moving regenerator also increases pressure loss, and hence slightly reducing the net engine power. Overall, engine's performance, in terms of net output power and efficiency, is largely improved by the introduction of the moving regenerator. This study also examines the mechanism on how the moving regenerator achieves these effects and the influence of porosity on engine performance.